Acute Toxicity Test of White Turmeric Extract (Curcuma Zedoaria) on Female Wistar Rat Endometrium - Wardhani, Fiska Maya; Florenza, Audrey Gracella; Erny Tandanu; Azizoğlu, Azizoğlu (Journal La Medihealtico, 2023)
Indonesia is a country that has very abundant natural biota resources. There are many types of plants that are often used in traditional medicine. One of the plants that is often used is white turmeric (Curcuma zedoaria). This study aimed to identify the toxic effects and determine the LD50 value of white turmeric extract. In this study, rats were divided into six groups with per-oral administration of the extract. After the administration of the extract, 24 hours of toxicity symptoms were observed, then the number of dead rats was recorded. On the 15th day, uterine organs were taken for histopathology observation. Based on the results of the tests that have been carried out, no toxic effects were found in rats, with a pseudo-LD50 value of >2000mg/kgBB. The conclusion of this study wa that there is no significant difference in endometrial histopathology such as epithelial proliferation at a dose of 2000mg/kgBW white turmeric extract with other groups (p=0.529).